Carbon Credits and Additionality : Past, Present, and Future - World Bank Group (World Bank, Washington, DC, 2016)
Several PMR countries are developing crediting mechanisms for domestic markets. Some countries are developing crediting mechanisms with a view to exploring options for trading with other countries in the future. The concept of “additionality” has long been considered important in the context of these crediting mechanisms as it ensures that the emission reduction or removal that is credited would not have otherwise occurred. However, there are different approaches that have been used and are emerging as new crediting mechanisms are being designed and implemented. This paper clarifies the concept of additionality and its significance for crediting mechanisms; describes the different approaches that have been used to demonstrate or test additionality; and explores the implications of the evolving carbon markets on the application and importance of additionality.